Nilai-Nilai Cinta Kasih dalam Film Layar Lebar âRindu Kami PadaMuâ - Anggitya, Paramastu titis (KOMUNITAS, 2015)
ByÂ nature,Â everyÂ humanÂ beingÂ endowedÂ theÂ feelingsÂ ofÂ loveÂ inÂ differentÂ levels,Â thatÂ affects behaviorÂ andÂ viewÂ ofÂ loveÂ valuesÂ differences.Â TheÂ fadingÂ ofÂ loveÂ inÂ humanÂ beingsÂ today encourages various efforts to place love compassions in human life. Through a film titled âRindu Kami PadaMuâ, longing of love shown by using certain symbols which is not easily understood byÂ theÂ audienceÂ atÂ aÂ glanceÂ asÂ effortsÂ toÂ placeÂ loveÂ compassions.Â ThisÂ studyÂ isÂ resultÂ ofÂ a qualitativeÂ researchÂ usingÂ RolandÂ BarthesÂ semioticÂ analysisÂ approachÂ andÂ RobertÂ Sternbergâs typology of love theory. The result showed that âRindu Kami PadaMuâ is a film that reflects the longing of love, including love for family, spouse,human beings, God and the environment. This filmÂ teachesÂ theÂ importanceÂ ofÂ loveÂ valuesÂ placementÂ inÂ universalÂ life.Â BasedÂ onÂ Robert Sternbergâs typology of love theory, it can be seenthat the types of love in this film consist of nonlove,Â liking,Â romanticÂ love,Â fatuousÂ love,Â andÂ consummateÂ loveÂ whichÂ areÂ variously experienced by all characters.